Cross-sectional interview study of fertility, pregnancy, and urogenital schistosomiasis in coastal Kenya: Documented treatment in childhood is associated with reduced odds of subfertility among adult women. - Sarah C Miller-Fellows; Laura Howard; Rebekah Kramer; Vanessa Hildebrand; Jennifer Furin; Francis M Mutuku; Dunstan Mukoko; Julianne A Ivy; Charles H King (Public Library of Science (PLoS), 2017)
Previous research has documented an increased risk of subfertility in areas of sub-Saharan Africa, as well as an ecological association between urogenital schistosomiasis prevalence and decreased fertility. This pilot project examined reproductive patterns and the potential effects of childhood urogenital Schistosoma haematobium infection and individual treatment experience on adult subfertility among women who were long-term residents in an S. haematobium-endemic region of coastal Kenya.We analyzed findings from 162 in-depth interviews with women of childbearing age in a rural, coastal community, linking them, if possible, to their individual treatment records from previous multi-year longitudinal studies of parasitic infections. Reproductive histories indicated a much local higher local rate of subfertility (44%) than worldwide averages (8-12%). Although, due to the very high regional prevalence of schistosomiasis, a clear relationship could not be demonstrated between a history of S. haematobium infection and adult subfertility, among a convenience sub-sample of 61 women who had received documented treatment during previous interventional trials, a significant association was found between age at first anti-schistosomal treatment and later fertility in adulthood, with those women treated before age 21 significantly less likely to have subfertility (P = 0.001).The high subfertility rate documented in this pilot study suggests the importance of programs to prevent and treat pelvic infections in their early stages to preclude reproductive tract damage. The available documented treatment data also suggest that early anti-schistosomal treatment may prevent the fertility-damaging effects of urogenital schistosomiasis, and lend support for programs that provide universal treatment of children in S. haematobium-endemic regions.